Safe guidewire visualization using the modes of a PTx transmit array MR system. Issue 6 (13th November 2019) - Godinez, Felipe; Scott, Greig; Padormo, Francesco; Hajnal, Joseph V.; Malik, Shaihan J.
Abstract : Purpose: MRI‐guided cardiovascular intervention using standard metal guidewires can produce focal tissue heating caused by induced radiofrequency guidewire currents. It has been shown that safe operation is made possible by using parallel transmit radiofrequency coils driven in the null current mode, which does not induce radiofrequency currents and hence allows safe tissue visualization. We propose that the maximum current modes, usually considered unsafe, be used at very low power levels to visualize conductive wires, and we investigate pulse sequences best suited for this application. Methods: Spoiled gradient echo, balanced steady‐state free precession, and turbo spin echo sequences were evaluated for their ability to visualize a conductive guidewire embedded in a gel phantom when run in maximum current modes at very low power level. Temperature at the guidewire tip was monitored for safety assessment. Results: Excellent guidewire visualization could be achieved using maximum current modes excitation, with the turbo spin echo sequence giving the best image quality. Although turbo spin echo is usually considered to be a high‐power sequence, our method reduced all pulses to 1% amplitude (0.01% power), and heating was not detected. In addition, visualization of background tissue can be achieved using null current mode, also with no recorded heating at the guidewire tip even when running at 100% (reported) specific absorption rate. Conclusion: Parallel transmit is a promising approach for both guidewire and tissue visualization using maximum and null current modes, respectively, for interventional cardiac MRI. Such systems can switch excitation mode instantaneously, allowing for flexible integration into interactive sequences.